Effect of EDTA and QMIX ultrasonic activation on the reduction of microorganisms and endotoxins in ex vivo human root canals - Matos, Felipe de Souza [UNESP]; Khoury, Rayana Duarte [UNESP]; Carvalho, Cláudio Antonio Talge [UNESP]; Martinho, Frederico Canato; Bresciani, Eduardo [UNESP]; Valera, Marcia Carneiro [UNESP] (FapUNIFESP (SciELO), 2019)
The present study aimed to compare the effectiveness of QMiX and 17% EDTA associated to passive ultrasonic irrigation (PUI) or manual agitation (MA) on the reduction of E. faecalis, E. coli and LPS from root canals. Forty single rooted human teeth were randomly divided into fourgroups(n=10),according to the final irrigation protocol: EDTA+MA,QMiX+MA,EDTA+PUI, QMiX+PUI. Sample collections were obtained from the root canal content immediately before preparation (baseline-S1), after instrumentation (S2), after final irrigation protocol (S3) and 7 days after instrumentation and final irrigation (S4). The antimicrobial effectivity and on endotoxin content were analyzed by culture procedure (CFU/mL) and LAL assay (EU/ mL), respectively. The results were statistically analyzed by Kruskal-Wallis and Friedman test (α=5%). QMiX+MA and QMiX+PUI reduced 100% of E. coli and E. faecalis bacteria and also preventedE. faecalis regrowthat S4. EDTAsignificantly reducedE. coli, but itwas not effective in reducing E. faecalis. All protocols reduced EU/mL when compared to S1, however at S4 there was a significant reduction of EU/mL only in the QMiX+MA and QMiX+PUI groups in relation to S3 and S2, respectively. Final irrigation with QMiX associated with MA or PUI had superior antibacterial efficacy compared to EDTA, eliminating 100% of E. coli and E. faecalis strains. In addition, QMiX+PUI reduced 97.61% of the initial content of LPS.
Keywords: Bacteria; Endotoxin; Passive ultrasonic irrigation; QMix root canal irrigant